Investigating reproductive life plan in pregnant women referred to teaching hospitals of Mashhad, Iran - Fatemeh Ghaffari Sardasht; Afsaneh Keramat; Zahra Motaghi (Wolters Kluwer Medknow Publications, 2021)
Background: Reproductive Life Planning (RLP) is a person-centered approach that investigates the reproductive needs, values, and priorities of each person and not only reduces the risk of unwanted pregnancies but also improves pregnancy outcomes and childbirth by investigating the health behaviors and underlying diseases of each individual. Therefore, the present study was conducted to assess RLP in pregnant women. Materials and Methods: This descriptive cross-sectional study was carried out on 1019 pregnant women who were referred to outpatient clinics of teaching hospitals in Mashhad, Iran, during May-August 2019. The participants were selected using a convenience sampling method. The data collection tool used was a questionnaire. Data analysis was performed in SPSS software. Results: The results of this study showed that about two-thirds of the participants had a plan for their reproductive years. The age range of the participants was 13-47 years. Among the women, 38.60' had experienced failure of contraceptive method, and 32.20' had an unmet need for family planning-Ž. Moreover, only one-third of the women had been referred for preconception care, but 88.70' of the pregnant women had their initial prenatal care visit in their first trimester. Conclusions: Given the considerable number of unwanted pregnancies and unmet needs for family planning in the present study, the modification of family planning policies seems necessary. Various strategies have been proposed to prevent unintended pregnancies such as RLP. The long-term goals of RLP are to plan pregnancies and improve maternal and infant outcomes.